Understanding Australian Community ABI Therapists' Preferences for Training in and Implementing Behaviour Interventions: A Focus on Positive Behaviour Support. Issue 2 (21st September 2020) - Carmichael, Jai Jason; Gould, Kate Rachel; Hicks, Amelia J.; Feeney, Timothy J.; Ponsford, Jennie Louise
Abstract: Objective: Individuals with acquired brain injury (ABI) may experience persistent and distressing challenging behaviours (CB), and therefore, effective delivery of behaviour interventions is crucial. This study aimed to investigate community ABI therapists' experiences of using, training in and implementing behaviour interventions with a focus on Positive Behaviour Support (PBS). Methods: A sample of Australian community ABI therapists ( n = 136) completed an online survey about their experiences with behaviour interventions, including PBS. Data from open-ended questions were analysed using content analysis. Frequency and descriptive statistics were computed, and a multiple regression was performed to determine factors predicting readiness to learn and implement new behaviour interventions. Rank-based non-parametric tests were conducted to investigate the influence of clinical role on experiences with behaviour interventions and training preferences. Results: Consistent with PBS, participants indicated that the following were important in addressing CB: teamwork and collaboration, person-centred practice, working with antecedents, environmental modification, improving quality of life and skill-building. Despite a high level of desire and readiness, 80% of participants reported facing barriers to learning and implementing new behaviour interventions (e.g., lack of time). Participants' confidence in using behaviour interventions (β = 0.31; p = 0.002) and the number of barriers faced (β = −0.30; p = 0.002) predicted their readiness to learn and implement new behaviour interventions. Confidence, duration of past training in behaviour interventions and preferred duration of future training did not differ based on clinical role. Conclusion: Implications for the development of training in behaviour interventions such as PBS and implementation into community practice are discussed.